Estimating active cases of Covid-19 post-school reopening in Malaysia using S-I-R modelling - Azrul Azim Mohd Yunus; Shahrina Ismail; Arif Asraf Mohd Yunus; Muhammad Safwan Ibrahim; Shaharudin Ismail (AIP Publishing, 2024)
Indexed by Scopus